Eco Printing of Palm Leaves as an Environmentally Friendly Efficiency of Oil Palm Plantations - Nurmin Nurmin; Dini Nur Astuti; Oktavia Yanti; Noer Setyadji; Subakho Aryo Saloko (Akademi Komunitas Perkebunan Yogyakarta, 2023)
Oil palm has dark green leaves, the leaves are pinnate, arranged in rosettes at the end of the stem. Oil palm leaves can be used as animal feed, apart from that, palm leaves can also be used as ecoprinting or as natural dyes to make patterns, motifs, as natural screen printing without the use of chemicals, which are environmentally friendly raw materials. Ecoprinting can be used as an alternative / way to reduce environmental and ecosystem damage. This research produces an alternative choice of using natural dyes by utilizing patterns/patterns of palm leaves as a raw material for coloring that can be applied to paper or cloth media. The results of this study were to determine the effect of the type of substance in palm leaves on the direction of color in the coloring of the Ecoprinting technique using oil palm leaves with white cloth. In the research process, he was able to produce a product catalog containing research results on the Ecoprint coloring technique using palm leaf patterns.